2010
DOI: 10.2478/v10019-010-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cranial irradiation in patients with small-cell lung cancer: the experience at the Institute of Oncology Ljubljana

Abstract: BackgroundProphylactic cranial irradiation (PCI) has been used in patients with small-cell lung cancer (SCLC) to reduce the incidence of brain metastases (BM) and thus increase overall survival. The aim of this retrospective study was to analyze the characteristics of patients with SCLC referred to the Institute of Oncology Ljubljana, their eligibility for PCI, patterns of dissemination, and survival.Patients and methodsMedical charts of 357 patients with SCLC, referred to the Institute of Oncology Ljubljana b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…might be due to the relatively small number of patients with brain metastases in both trials as well as due to possible differences in other patients’ characteristics. It is well known that the extent of the disease, characterized by performance status, LDH levels and the number of metastatic sites, determines the prognosis of ED even more than the site of metastases 1619. The percentage of patients with brain metastases in our collective of patients was rather low (13.5%) which might be the consequence of our selection criteria, i.e.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…might be due to the relatively small number of patients with brain metastases in both trials as well as due to possible differences in other patients’ characteristics. It is well known that the extent of the disease, characterized by performance status, LDH levels and the number of metastatic sites, determines the prognosis of ED even more than the site of metastases 1619. The percentage of patients with brain metastases in our collective of patients was rather low (13.5%) which might be the consequence of our selection criteria, i.e.…”
Section: Discussionmentioning
confidence: 83%
“…It was followed by a large EORTC (European Organisation for Research and Treatment of Cancer) trial that confirmed significant benefit of PCI in all patients achieving response (complete or partial) to first-line systemic therapy 25. Based on these observations PCI represents a standard treatment approach nowadays, which ultimately results in a lower rate of brain metastases diagnosed during the course of the disease 19. However, the percentage of patients presenting with brain metastases at the time of diagnosis remains stable, i.e .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent retrospective report also indicated a 25% incidence in the development of brain metastasis after PCI (22,23). Moreover, when PCI was not performed for patients with completely surgically resected SCLC, the actuarial risk of developing brain metastasis was reportedly 13.8% at 1 year and 23.0% at 3 years (18).…”
Section: Discussionmentioning
confidence: 98%
“…Survival after the whole brain radiation therapy ranges from 10 to 18 months, but was reported to rise to an average of 44 months following chemotherapy and radiation therapy, or chemotherapy alone 1319. Yet, radiation therapy is associated with a high incidence of neurotoxicity, which is however not seen after the radiation therapy of patients with brain metastases of solid tumors because of their shorter survival or lower tumor dose 20. Although currently available therapeutic regimes prolong the survival, they are in contrast to therapies used to treat systemic lymphomas,21,22 not curative in most patients.…”
Section: Introductionmentioning
confidence: 99%